Fractional Chemical Composition of Asphalt as a Function of Its Durability - Kassir, A.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In order to get better understanding of asphalt pavement performance, asphalt from five Iraqi refineries (Qayarah, Nassiriyah, Baiji, Samawah and Daurah) were analyzed into five chemical fractions including asphaltenes, polar compounds, first acidaffins, second acidaffins and saturated hydrocarbons where the last four fractions called maltenes. Polar compounds /saturated hydrocarbons ratio (PC/S) and the ratio of the reactive to the unreactive components of the maltenes fraction (durability rating) parameters were determined. The study showed that Baiji asphalt has the best durability over other asphalts, while Qayarah asphalt is considered to have the least durability grade. These results confirm the correlation of the chemical composition of asphalt as a function of its durability.